1985
DOI: 10.1039/c39850000974
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of NH2terminal tyrosyl–peptide bonds using hypervalent iodine

Abstract: The cleavage of NH2-tyrosine dipeptides with C6H51(OAc)2-MeOH-KOH yields 4-(methoxymethyl)phenol.We report a specific cleavage reaction of NH2-terminal tyrosyl peptides as expressed in Scheme 1 and summarised in Table 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…1b). 42 The bond scission occurred between the C a and C b of the Tyr residue in intermediate 6, generating 4-methylenecyclohexadienone (7) which was then converted to the Nterminal fragment 4-(methoxymethyl)phenol (8) in presence of MeOH. Concomitantly, an intact C-terminal amino acid 9 was obtained from an acyl cyanide species 11 aer hydrolysis and decarboxylation (Fig.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…1b). 42 The bond scission occurred between the C a and C b of the Tyr residue in intermediate 6, generating 4-methylenecyclohexadienone (7) which was then converted to the Nterminal fragment 4-(methoxymethyl)phenol (8) in presence of MeOH. Concomitantly, an intact C-terminal amino acid 9 was obtained from an acyl cyanide species 11 aer hydrolysis and decarboxylation (Fig.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Amino acid 11k is subjected to decarboxylation upon treatment with phenyliodine( iii ) diacetate to give an imine 11l . 61,62 The imine 11l formed could be oxidized to nitrile 11n in the presence of an excess amount of oxidant. Transimination 63 of imine 11l takes place with the iodonitrene to give 11m , 14 which reacts with the second moiety of the iodonitrene via insertion to give the diaziridine intermediate 11o .…”
Section: Synthesis Of Terminal Diazirines From Amino Acids Through Ta...mentioning
confidence: 99%
“…16 To explore the possibility of using other hypervalent iodine reagents we carried out all the above reactions using a catalytic amount of sodium azide and hypervalent iodine reagents such as IBX, KIO 3 , and 4,4¢-bis(dichloroiodo)biphenyl in place of the (diacetoxyiodo)benzene, but no formation of benzaldehyde, ketone, and nitrile was observed even after long reaction times.…”
mentioning
confidence: 99%
“…Scheme 2 Ketone and nitrile by decarboxylation using (diacetoxyiodo)benzene and catalytic sodium azide Whilst we observed that (diacetoxyiodo)benzene alone is inactive, it has been reported that, with a-amino aryl carboxylic acids, in situ generation of PhI(OCH 3 ) 2 using (diacetoxyiodo)benzene and KOH in methanol can used for nitrile formation, but low yields were reported, and the method works only for p-hydroxyaryl substrates. 16 To explore the possibility of using other hypervalent iodine reagents we carried out all the above reactions using a catalytic amount of sodium azide and hypervalent iodine reagents such as IBX, KIO 3 , and 4,4¢-bis(dichloroiodo)biphenyl in place of the (diacetoxyiodo)benzene, but no formation of benzaldehyde, ketone, and nitrile was observed even after long reaction times.…”
mentioning
confidence: 99%
See 1 more Smart Citation